Australian Anglicans and Religious Plurality: Exclusive Theologies vs. Theological Affirmations of Diversity - A Tale of Two Cities - Bouma, Gary D. (Journal for the academic study of religion, 2013)
Religious Diversity both within and between religious groups has long challenged Anglicans. The demographics of religious diversity shape interreligious relations. Societies where one group dominates numerically and adds to this cultural domination and state support are very different from societies where no one group dominates. In Australia, Anglicans have been one group among others, sharing state support in the early nineteenth century and civic recognition today. Australian sectarian rivalries of the nineteenth and early twentieth centuries occasioned both alliances among Protestant groups anticipating and advancing ecumenism, and bitter anti-Catholic division. Meanwhile internal religious diversity among Anglicans seemed to exceed the differences between them and others. The logic and behaviours of ecumenism were extended by some to Muslims, Buddhists, Hindus and others; while exclusivist theologies prevailed in other quarters. The demographics of religious diversity are now felt in nearly every city in the world. This is particularly true of Australia's largest cities, Sydney and Melbourne. This plurality not only enables everyday encounters between people of many faiths, but calls for the completion of the theological work begun by Bishop Kenneth Cragg and others; theological work that moves through mutual respect and recognition of irreducible difference to accepting religious diversity as part of the orders of creation and discerning Jesus' respect for religious diversity in the Gospels. This article provides data on the Australian experience; recounts the development of interreligious relations through the lens of a comparison of Melbourne and Sydney; and does some biblical and theological work toward valuing God's gift of religious diversity.